THE ROLE OF STATISTICS IN RESEARCH TO IMPROVE CRITICAL THINKING SKILLS - Sri Rahayu Pudjiastuti (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2022)
Statistics is a science of collecting, processing, presenting, analyzing and interpreting data obtained into information to assist in making effective decisions. Statistics can also be used as a tool to facilitate the calculation of data in the form of numbers. In social research that is quantitative in nature, the role of statistics is very large. Starting from before the research, when conducting research to processing research data. The statistical process begins with sampling techniques, validity and reliability tests, hypothesis testing, data analysis and interpretation. Preliminary data presentation used descriptive statistics to prove quantitatively. Statistical literacy skills will improve critical thinking skills. Critical thinking is defined as an attitude of wanting to think deeply about problems and things that are within one's reach; knowledge of logical methods and reasoning. This study concluded that the ability to think critically in learning statistics to stimulate analytical skills in understanding statistics lessons and being able to implement statistics lessons in conducting research.